Сultural and Historical Conditions of Ukrainian Language Development in Czechoslovakia in the Interwar Period (Linguostylistic Studies, 2016)
The article is devoted to the analysis of extralinguistic factors, which influenced greatly functioning and development of different styles of Ukrainian literary language on the territory of Czechoslovakia in the interwar period. The emphasis is laid on the Ukrainian diaspora activities, which became a powerful center of modern Ukrainian literary language development. The author makes an attempt to analyze and evaluate the role of major local cultural centers of Ukrainian emigration (Ukrainian Free University, Ukrainian Academy of households, numerous periodical publications, etc.), and also the impact of civil society organizations on the development of the Ukrainian literary language. Key words: literary Ukrainian, political emigration, Czechoslovakia, interwar period, Ukrainian Civic Committee, Ukrainian Free University, Ukrainian sources. References